If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 7 = 57 Reorder the terms: 7 + 25x = 57 Solving 7 + 25x = 57 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 25x = 57 + -7 Combine like terms: 7 + -7 = 0 0 + 25x = 57 + -7 25x = 57 + -7 Combine like terms: 57 + -7 = 50 25x = 50 Divide each side by '25'. x = 2 Simplifying x = 2
| 3*3*3*76=x | | 3*3*3*76= | | 2+14z=-8+9z | | 23m-43x=61 | | 3c-15=17-c | | 9+4=1 | | 7-2x=-11 | | 4+3x=4(2x+6) | | 8x+7+9x-4=180 | | W(w+4)=77 | | 2+5t-3=34 | | 2x-9+4=9x+39 | | 0.1y=8 | | 5(3x-4)=11 | | 2x^2+36x+162=0 | | 3xy+10+5x+6y= | | 27x^2+144s+192=0 | | x^3-x^2-20x=0 | | x^3+2x^2-35x=0 | | .8y=8 | | x^3-x^2-12x=0 | | .08y=8 | | 4(x+8)=7(x+2) | | 3x+5=2x+6 | | 6-5(x-2)=3 | | 5x+2-3x=8+4-6 | | 5r^2=26r+24 | | 6x+13=2x+7 | | a^2+10a+16=0 | | 3x-5=8X-5 | | -5x+2x-22x=75 | | 7-3x=2x |